Близкие, далекие: Давид Бурлюк и А. Ветлугин [Close, Distant: David Burliuk and A. Vetlugin] - Belobrovtseva, Irina (Slavica Revalensia, 2026)
The article addresses a short (1923—1925) but at the same time extremely important period in the shaping of destinies of two Russian émigrés—artist and poet David Burliuk and journalist, prose writer and figure of the American film industry A. Vetluguin (Vladimir Ryndziun). What makes them alike is the very choice of the destination country (the US), which was uncommon for post-revolutionary refugees from Russia, and in the fact they worked for the same New York Russian newspaper. What sets them apart, however, is their different attitudes towards America, Americanism and their entirely polar answers to the question of whether to integrate into the American society or not.